Association of Preoperative Neutrophil/Lymphocyte Ratio with Clinical Outcomes in Dedifferentiated Chondrosarcoma Patients - Liu C; Xing Y; Jiao Q; Yang Q; Yu W; Li Y; Tao X; Yao W (Cancer Management and Research, 2020)
Chenglei Liu1 ,* Yue Xing2 ,* Qiong Jiao,3 Qingcheng Yang,4 Wenbin Yu,5 Yuncheng Li6 ,* Xiaofeng Tao,1 Weiwu Yao7 1Department of Radiology, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Radiology, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai, People’s Republic of China; 3Department of Pathology, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai, People’s Republic of China; 4Department of Orthopaedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai, People’s Republic of China; 5Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education), Department of Head and Neck Surgery, Peking University Cancer Hospital & Institute, Beijing, People’s Republic of China; 6Department of Otorhinolaryngology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 7Department of Radiology, Shanghai Tongren Hospital, Shanghai JiaoTong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiwu YaoDepartment of Radiology, Shanghai Tongren Hospital, Shanghai JiaoTong University School of Medicine, Shanghai, People’s Republic of ChinaEmail yaoweiwuhuan@163.comXiaofeng TaoDepartment of Radiology, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of ChinaEmail cjr.taoxiaofeng@vip.163.comBackground: Dedifferentiated chondrosarcoma (DC) is an extremely uncommon malignant bone tumor with dismal survival outcomes. The purpose of this study was to investigate whether the preoperative neutrophil/lymphocyte ratio (NLR) has the ability to predict overall survival (OS) in DC patients.Materials and Methods: Twenty-three DC patients with surgical resection were retrospectively reviewed between 2008 and 2015. The clinical pathological information and survival data were collected for analysis. The cut-off point for NLR was defined by receiver operating curve (ROC). The impact of NLR level on OS between two groups was compared using Kaplan–Meier curves with the Log-rank test. The association between NLR and OS was calculated by univariate and multivariate Cox proportional models.Results: From the ROC analysis, the optimal NLR cut-off point was 3.11. Patients with high NLR had a worse OS than low NLR (p = 0.003, Log-rank test). In univariate analysis, a significant association was observed between high NLR and poor OS (Hazard ratio (HR) 4.62, 95% confidence interval (CI) 1.48– 14.34, p = 0.008). After adjustment of co-variables, high NLR had more than 4 times the risk of mortality (HR 4.01, 95% CI 1.12– 14.26, p = 0.032).Conclusion: Preoperative NLR in peripheral blood is an easily accessible and cost-effective prognostic biomarker in DC patients. A prospective study with large sample size is warranted.Keywords: dedifferentiated chondrosarcoma, neutrophil/lymphocyte ratio, outcome, prognostic factor